Holding Hands with Bacteria The Life and Work of Marjory Stephenson - Štrbáňová, Soňa.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This biographical brief outlines the remarkable life and career of British biochemist, Marjory Stephenson (1885-1948). In nine concise chapters, Štrbáňová describes Stephenson's scientific accomplishments and sets these against the socio-political challenges of the time. Stephenson played an important role in the development of biochemistry and molecular biology. She was one of the first scientists to use microorganisms as models for research into cellular biochemical processes and their regulation. Later she went on to coin the term chemical microbiology, which was communicated in her monograph and textbook "Bacterial Metabolism" (1930-1949). Stephenson also actively participated in the establishment of the institutionalized interdisciplinary field of general microbiology which integrated research into diverse forms of microorganisms at various levels of organization. Alongside these scientific achievements, Štrbáňová outlines Stephenson's constant battle with practices of undeclareddiscrimination, her important role as one of the first women science managers  and organizers, and her influential position within the scientific community. A scientist of great merit and a role model to women scientists of all disciplines, the life of Marjory Stephenson is of interest to biochemists, molecular biologists, historians of the chemical and biological sciences, and women scientists of all generations.
Early Years -- Becoming Hopkins' Associate -- Fruitful Years: What Alice Found in the Microbes -- Between the Medical Research Council and the Biochemistry Department -- The Rise of Nazism in Germany and the Second World War -- Post-war Activities: Recognition and Honours -- From Chemical Microbiology to General Microbiology -- Stephenson's personality -- Conclusions: What is Left Behind.... -- Supplements.
Keywords: Chemistry -- History; Science -- History; Microbiology; History of Chemistry; History of Science; Microbiology